1987
DOI: 10.1104/pp.84.4.972
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transglutaminase Activity in Plant Tissue

Abstract: An extract prepared from the apical meristematic region of etiolated pea seedligs was able to catalyze the incorporation of putrescine into trchloroacetic acid precipitable material. The enzyme was found to be soluble and followed a typical Michaelis-Menten kinetics when N-Ndimethyl casein was used as a substrate. Its activity was promoted by Ca2 We present here, for the first time, evidence indicating that an enzyme with characteristics similar to those found in most transglutaminases described so far is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
53
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 11 publications
6
53
0
1
Order By: Relevance
“…In addition, studies with sea urchins during embryogenesis showed that post-translational modification of protein by polyamines is mediated by transglutaminase (4). Transglutaminase and other polyamine-binding enzyme activities have recently been reported in plant tissue (10,20). Although our data do not provide direct evidence that binding of Spd to protein is mediated via transglutaminase, they are consistent with this possibility (25).…”
supporting
confidence: 73%
“…In addition, studies with sea urchins during embryogenesis showed that post-translational modification of protein by polyamines is mediated by transglutaminase (4). Transglutaminase and other polyamine-binding enzyme activities have recently been reported in plant tissue (10,20). Although our data do not provide direct evidence that binding of Spd to protein is mediated via transglutaminase, they are consistent with this possibility (25).…”
supporting
confidence: 73%
“…TGase activity in plants was fi rst observed in pea seedlings [Icekson and Apelbaum 1987], and subsequently found in organs of both lower and higher plants. Signorini et al [1991] identifi ed TGase activity in the leaves of silver beet (Beta vulgaris L.).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, TGases are known to be widely distributed in nature, being found in mammalian, vertebrates, invertebrates, mollusks, plants, and microorganisms (Folk et al 1980;Icekson and Apelbaum 1987;Porta et al 2013;Yasueda et al 1994), and were reported as a single-chain polypeptide consisting of 331 amino acids (Della Mea et al 2004;Macedo and Sato 2005).…”
Section: Introductionmentioning
confidence: 99%